The Impact of Islamic Religious Learning Assistance on The Reliciency of Single Parentage and the Role of Spiritual Well-Being - Nuruddin, Nuruddin; Muis, Abd; Muniron, Muniron (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
After the Covid-19 pandemic, parents were increasingly involved in assisting children's learning, from explaining material children did not understand to responding well to all learning from school. This article aims to analyze and measure the role of intervening spiritual well-being in the influence of religious learning assistance on single-parent resilience during the Covid-19 pandemic in the Horseshoe Region of East Java Province. This study involved 150 single-parent mothers/parents. All participants completed an online survey of a parent's resilience index, assistance in religious learning, and spiritual well-being. The study results show that 1) The better the mother's assistance in the learning process to accompany the child's learning assignments, the higher the spiritual well-being relationship with oneself is believing that life has several goals with an influence of 77.3%. 2) The better the mother's assistance in the learning process to accompany the child's learning assignments, the better the resilience of single mothers in dealing with all situations, with an effect of 48.0%. 3) the higher the spiritual well-being relationship with oneself is believing that life has several goals, the better the resilience of single mothers in dealing with all situations, with an influence of 40.6%.